P02.06 De-novo ceramide synthesis in skull base chordomas suggests a correlation with tumor proliferation. (19th September 2018) - La Corte, E; Patanè, M; Calatozzolo, C; Maderna, E; Raggi, A; Dei Cas, M; Paroni, R; Ghidoni, R; Ferroli, P; Pollo, B
Abstract: Background: Skull base chordomas are rare slow-growing neoplasms that arise from notochord. Their morbidity is mainly related to highly aggressive local invasion and resistance to treatments. There isn't bio-marker representing its heterogeneous appearance. Lipidomics is emerging as a new approach in many cancers and it has never been applied in chordomas. Our aim is to investigate chordoma biological behavior and the role of ceramides production in this context of proliferation and invasion. Material and Methods: A prospective analysis has been performed on 15 frozen and paraffin-embedded skull base chordomas surgically treated at our Institution from 2016 to 2018. Clinical, radiological and pathological data were collected. The expression of Brachyury, cMET, PDGFR-β, cKIT, β-catenin, Filamin-A, GAB1, YKL-40, TERT was assessed by immunohistochemistry. Sphingolipids were extracted from frozen tissues and ceramides and dihydroceramides pattern was evaluated by HPLC/MS-MS. The autophagy and apoptosis pathways were also evaluated by assessing the expression of p62, bcl-2, beclin-1 and LC3-II by immunohistochemistry and western blot; transmission electronic microscopy was also performed in two cases. Results: The histological analysis confirmed the clinical and radiological diagnosis of chordoma in all the cases. Total ceramides and dihydroceramides levels were concomitantly more elevated especially in recurrent tumors that underwent previous surgical resection and radiation therapy in comparison to the primary ones (p<0.01). Dihydroceramides elevation suggested the activation of the de-novo ceramide synthesis pathway. Total ceramides levels also correlated with MIB-1 staining (r 2 =0.586, β=0.765, p<0.01). Chordomas with high proliferation index and higher ceramides content showed to have also an autophagy pathway activation. Conclusion: A thorough lipidomics analysis has never been conducted in chordomas. De-novo ceramides synthesis seems to be higher in mostly recurrent already irradiated chordomas. Ceramide elevation could be related to both radiation stress response and autophagy pathway activation in the subgroup of high-proliferative chordomas. Cytoprotective autophagy may explain the need of chordoma cells to prolong their survival rate. Such results should be validated in future larger clinical, in-vitro and in-vivo studies to confirm such intricate link between ceramides, autophagy and tumor proliferation rate.